Dilema dalam Kebijakan Negara dan Keamanan Manusia: Kasus Kebijakan India pada Pemerintahan Narendra Modi, Perdana Menteri India - Alrafsya Mahendra Saputra (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2018)
India is a country that is known for its attachment to its culture, but on the other hand, what is unknown to the wider community is the existence of human rights violations caused by its own government under the leadership of Narendra Modi. What the author will say in this case is about Narendra Modi's policy in solving social and economic welfare issues. His welfare policy is how he resolves social conflicts, social security, and his economic policies to be examined is how he promoted India as an industrialist state can undermine the protection of his human rights.